The effect of liquidity, solvency, and profitability on company value in retail sub-sector companies listed on the Indonesia stock exchange for the 2019-2023 period - Adha, Shultonnyck; Putri, Agatha Patricia Eka; Savitri, Arina Kamalia (Privietlab, 2026)
This study aims to determine the influence of liquidity, solvency, and profitability on the value of the company. The population in this study is retail sub-sector companies listed on the Indonesia Stock Exchange. Based on the sampling technique with purposive sampling, a sample of nine companies was obtained. The data were analyzed using multiple linear regression analysis with the help of SPSS version 30. The results of the study show that partially liquidity and profitability do not have a significant effect on the company’s value, while solvency has a positive and significant effect on the company’s value. The results of the study simultaneously show that liquidity, solvency, and profitability have a positive and significant effect on the company’s value.